Pengaruh Skeptisisme, Locus Of Control, Job Stress, Self-Efficacy, Kompleksitas Tugas, dan Obedience Pressure Terhadap Audit Judgment: Studi Empiris Pada Auditor di Kantor Akuntan Publik Kota Medan - Amyra Putri Wahyuzan; Yulita Triadiarti (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
The purpose of this research is to examine how auditors' professional scepticism, locus of control, job stress, self-efficacy, process complexity, and obedience pressure affect their audit judgement while they are employed by KAP in Medan City. The researchers in this study used SPSS to conduct multiple linear regression analyses on survey data collected from auditors. The methodology was based on a quantitative approach. Job stress and task complexity did not demonstrate a significant effect on audit judgement, but professional scepticism, locus of control, self-efficacy, and obedience pressure did. All the independent variables have a notable impact on audit judgement at the same time, suggesting that auditors' audit judgement is heavily influenced by psychological factors and compliance pressure